A Comparative Study of Capacitated Vehicle Routing Problem Heuristic Model - Chandra, Agung; Naro, Aulia (International Journal of Engineering and Emerging Technology; Vol 5 No 2 (2020): July - December, 2020)
CVRP is a variant of VRP that can be used to find the minimum distance and number of vehicles. In this paper, three algorithm for initial solutions are compared to find the minimum distance for shipping goods from distribution center to all outlets routinely in West Jakarta – Improved Clarke and Wright (ICW) algorithm, Karagul Tokat Aydemir (KTA) algorithm , and Sweeping – Cluster First Route Second algorithm. The results show that Sweeping algorithm is the shortest total distance compared to other two algorithm which is 48.57% shorter than KTA algorithm and 33.33% shorter to ICW algorithm. Larger sample sizes need to be evaluated to strengthen this findings.   Index Terms —CVRP, ICW, KTA, Sweeping algorithm